Safer sex or pleasurable sex? Rethinking condom use in the AIDS era - Khan, S.; Hudson-Rodd, N.; Saggers, Sherry; Bhuiyan, M.; Bhuiya, A. (CSIRO Publishing, 2004)
Background: Condom use in Bangladesh is low despite nationwide family planning initiatives and HIV interventions. Methods: Fifty men aged between 18 and 55 years from diverse socio-demographic backgrounds and five key informants were interviewed in a qualitative male sexuality study. Results: Refusal to use condoms is not only a personal choice, but pertains to relationships. The meanings of reduced bodily pleasure associated with condom use are socially constructed. Men's emotions and trust expressed through understanding of direct penile-vaginal contact and ejaculation inside the vagina as 'pure' and 'natural' sex oppose condom use. Sexual prowess in the form of prolonged intercourse without condoms, as depicted in Western pornography, was perceived as a 'real man's' sexual skill. Men sought to preserve a 'good man's' image by avoiding condoms, which symbolised promiscuous men in AIDS educational mesages. Conclusion: Social dimensions of masculine sexuality, pleasure, eroticism and the emotional aspect of men's lives have to be addressed for effective condom promotion.